Gastronomic experiences on tourists life satisfaction and happiness : the case of Porto - Rodrigues, Paula (2023)
The tourists' gastronomic experiences are important in developing a destination branding strategy, especially if this translates into greater happiness and tourists' life satisfaction. We intend to study the influence of five gastronomic/food experience variables on the tourists’ life satisfaction and happiness. After inquiring 352 tourists in Porto, the data were analysed through SEM and SPSS/AMOS software. The results validate the hypotheses concerning refreshment and hedonic/novelty experiences, which improve tourists’ satisfaction and happiness. The adverse experiences reduce the tourists' happiness, and lastly, tourists' life satisfaction with the gastronomic/food experience improves their happiness. Theoretical and practical implications are discussed.